Effect of Student Teams Achievement Division and Vocabulary Mastery to Reading Comprehension Ability - Rahayu Fitri; Ninit Alfianika (Intelektual Pustaka Media Utama, 2017)
This research aimed to describe the effect of STAD technique and vocabulary mastery to reading comprehension ability. This is a quantitative research with quasi-experimental research with factorial design 2x2. Sampling was done by using simple random sampling technique. Data were collected by using objective tests. The results of this research were: (1) there was a difference in reading comprehension between students taught using STAD technique with conventional technique; (2) there was a difference in reading comprehension between students who had a high vocabulary taught by STAD technique type with students having high vocabulary taught using conventional technique; (3) there was a difference in reading comprehension between students who had low vocabulary are taught using STAD technique with students who had low vocabulary taught using conventional technique; and (4) there was an interaction between the use of STAD technique and vocabulary mastery in influencing the students reading comprehension ability.